Antitumor activity of Cuphea ignea extract against benzo(a)pyrene-induced lung tumorigenesis in Swiss Albino mice. (2019) - Hassan, Sherien K.; Mousa, Amria M.; El-Sammad, Nermin M.; Abdel-Halim, Abeer H.; Khalil, Wagdy K.B.; Elsayed, Elsayed A.; Anwar, Nayera; Linscheid, Michael W.; Moustafa, Eman S.; Hashim, Amani N.; Nawwar, Mahmoud
Highlights: Phenolic compounds from Cuphea ignea extract were identified. Chemopreventive and chemotherapeutic potentials of C. ignea extract were demonstrated in mice. Tumor, inflammatory, oxidative stress, apoptotic and angiogenic markers were investigated. Histopathological analysis showed improved lung tissues after treatment with C. ignea extract. Abstract: Lung cancer has one of the highest mortality rates among various types of cancer and is the most frequent cancer in the world. The incidence of lung cancer is increasing rapidly, in parallel with an increased incidence of smoking. Effective chemoprevention may be an alternative strategy to control the incidence of lung cancer. Thus, the objective of current work was to ascertain the possible preventive and therapeutic efficacies of Cuphea ignea extract in a mouse model of lung tumorigenesis and its cytotoxicity toward the A549 human lung cancer cell line. Lung tumorigenesis was induced by the oral administration of benzo(a)pyrene (50 mg/kg b.w.) twice per week to Swiss albino mice for 4 weeks. Benzo(a)pyrene-treated mice were orally administered C. ignea (300 mg/kg body weight, 5 days/week) for 2 weeks before or 9 weeks after the first benzo(a)pyrene dose, for a total of 21 weeks. At the end of the administration period, various parameters were measured in the serum and lung tissues. The results revealed that the oral administration of benzo(a)pyrene resulted in increases in relative lung weight, serum levels of tumor markers (ADA, AHH, and LDH), and the inflammatory marker NF-κB, and a decreased total antioxidant capacity compared with the control. In addition, decreased levels of enzymatic and non-enzymatic antioxidants, with a concomitant increase in lipid peroxidation, metalloproteinases (MMP-2 and MMP-12), and the angiogenic marker VEGF were detected in lung tissues. Moreover, benzo(a)pyrene administration induced the upregulation of PKCα, COX-2, and Bcl-2 expression, with the downregulation of BAX and caspase-3 expression. C. ignea treatment alleviated all alterations in these parameters, which was further confirmed by the histopathological analysis of lung tissues. The findings of the current work provide the first verification of the preventive and therapeutic potentials of C. ignea extract against benzo(a)pyrene-induced lung tumorigenesis in mice.